Analisis Sistem Pengendalian Internal COSO atas Siklus Persediaan Bahan Baku pada Perusahaan Dimsum Frozen Food - Suci Sekar Arum Sari Anggraini; Ali Farhan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Reliable internal control serves as the foundation for sound financial governance in any type of business organization, including small and medium-sized enterprises in the food processing industry. This article presents the findings of an internship-based study conducted at a frozen dim sum manufacturing company located in Pondok Candra, Sidoarjo Regency, East Java. The study primarily focuses on analyzing the implementation of the internal control system within the raw material inventory cycle and evaluating the extent to which these practices align with the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. A descriptive qualitative approach was employed, utilizing data collection techniques such as direct observation, in-depth interviews with the production manager and warehouse staff, and a review of internal company documents. The study concludes that the frozen dim sum company’s control system is reasonably effective in terms of COSO framework alignment, although there remain certain gaps that require improvement.